(untitled) (European Journal of Education and Psychology, 2020)
The objective of the study was to translate, adapt and evaluate the evidence of construct and concurrent validity of an instrument that measures the mechanisms of moral disengagement in school adolescents. The evidence of concurrent validity with the role of spectator-encouraging of the aggression is analyzed. 1,212 students from 10 public high schools from five municipalities of a northwestern state of Mexico participated. 54.4% are women and 45.6% are men, whose age range is between 11 and 15 (M age = 13.08, SD = .95 years). A measurement model that confirms concurrent validity with acceptable internal fit indicators was obtained. The results are discussed in terms of their usefulness for identifying the construct in a particular cultural ecosystem and for contextualized analysis. It is concluded that the scale has adequate psychometric properties for the measurement of moral disengagement in adolescents, specifying, in addition, a contribution to the study of violence and school bullying.